The role of morphological traits in predicting the functional ecology of arboreal and ground ants in the Cerrado–Amazon transition - Almeida, Rony P. S.; Teresa, Fabrício B.; Camarota, Flávio; Izzo, Thiago Junqueira; Silva, Rogério R.; Andrade-Silva, Joudellys; de Arruda, Filipe Viegas (Oecologia, 2023)
There is often a vertical stratification of the vegetation in tropical forests, where each forest stratum has a unique set of environmental conditions, including marked differences in habitat heterogeneity, physical complexity, and microclimate. Additionally, many tropical forests are highly seasonal, and we need to consider the temporal variation in environmental conditions when assessing the functional aspects of their organisms. Here, we tested the hypothesis that vertical stratification and seasonality shape tropical ants’ functional ecology and that there are differences in the functional trait diversity and composition between arboreal and ground-dwelling ant communities. We collected ants in the arboreal and ground strata in the rainy and dry seasons in six different areas, measuring seven morphological traits to characterize their functional ecology and diversity. Irrespective of the season, we found a distinct functional composition between arboreal and ground-dwelling ants and a higher functional richness on the ground. However, ground ants were more functionally redundant than arboreal ants. The differences in functional richness and redundancy between ant inhabiting strata and season could also be observed in the community-weighted mean traits: arboreal and ground ant traits can be distinguished in Weber’s length, mandible length, eye length, and eye position on the head capsule. The differences in these functional traits are mainly related to the ants’ feeding habits and the complexity of their foraging substrates. Overall, by providing the first systematic comparison of continuous traits between arboreal and ground-dwelling ants, our study opens new investigation paths, indicating important axes of functional diversification of tropical ants.